Раманiвська спектроскопiя графено-подiбних наночастинок дисульфiдiв молiбдена i вольфрама - Naumenko, A.; Kulikov, L.; Konig, N. (Publishing house "Academperiodika", 2019)
The Raman spectra obtained in the case of graphene-like 2H-MoS2 and 2H-WS2 nanoparticles and depending on their average sizes in the [013] and [110] crystallographic directions are reported. It is established that the Raman spectra of graphene-like 2H-MoS2 nanoparticles and micron particles are closely related. Similarities of the Raman spectra point to the homogeneity of graphene-like 2H-MoS2 nanoparticles. The small shifts and the Raman spectrum line widening, for graphene-like 2H-MoS2 and 2H-WS2 nanoparticles, which are caused by the influence of the sizes of nanoparticles and their anisotropy, have been observed. The dependence of Raman spectra of graphene-like 2H-MoS2 nanoparticles on the their size in the crystallographic direction [110] is first shown, i.e. the positions of bands in the spectrum depend not only on the number of nanolayers S-Mo-S, but also on the size in the [110] direction.